Keadilan Restoratif dalam Penyelesaian Perkara Penyalahgunaan Narkotika Pasca Pedoman Jaksa Agung Nomor 18 Tahun 2021: Perspektif Teori Keadilan Bermartabat - Marune, Abraham; Hartanto, Brandon (The Prosecutor Law Review, 2023)
This paper assesses the impact and identifies areas of Indonesia’s Attorney General Guidelines Number 18 of 2021 concerning the Settlement of Narcotics Abuse Crime through Rehabilitation with a Restorative Justice Approach as the Implementation of the Dominus Litis Principle. The guideline emphasizes restorative justice, prioritizing rehabilitation over imprisonment for narcotics users. Utilizing a normative juridical approach, employing the dignified justice theory. The research finds that the guidelines embody the concept of restorative justice, aiming to resolve narcotics cases peacefully outside the courts. This aligns with the dignified justice theory, emphasizing divine values and human rights, so the Prosecutor's Office's role in promoting a balanced and conscientious approach to prosecution, aligning with the ideals of Pancasila in criminal cases, particularly drug-related offenses. The paper suggests prioritizing restorative justice, emphasizing a holistic perspective and the Prosecutor's Office's potential